REMOTE WORK AS A PROMISING FORM OF LABOUR ORGANIZATION FOR RUSSIAN ENTREPRENEURIAL STRUCTURES - I. Gurova (Модернизация, инновация, развитие, 2016)
Remote work (telecommuting) is one of the modern technologies of the organization of the labor process, which is not yet widely used in domestic practice. However, in times of crisis, when entrepreneurial structures seek for the maximum reduction of expenses, it can be a tool to address many of the pressing issues related to the most effective use of production and labor resources.The article discusses the features of the remote work on a world level and in our country, detected its strengths and weaknesses for the participants of labour relations, as well as revealed the potential of this form of labor organization for achievement of optimum balance between expenses and efficiency of entrepreneurial structures.